2023
DOI: 10.5114/pm.2023.127774
|View full text |Cite
|
Sign up to set email alerts
|

Early-stage cervical cancer treatment – what’s new?

Camilla Di Dio,
Ilham Azenkoud,
Angelo Trezza
et al.

Abstract: The gold standard of treatment for patients with early-stage cervical cancer is radical hysterectomy, in agreement with the entire scientific community. During the last decade, growing evidence has supported the minimally invasive approach. Several studies have suggested that the minimally invasive approach could improve surgical and perioperative outcomes. Because of these findings, ESCO/ESTRO/ESP guidelines state that a “minimally invasive approach is favoured” in comparison with open surgery, as a grade B r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
(141 reference statements)
0
3
0
2
Order By: Relevance
“…No entanto, essa abordagem traz consequências indesejáveis, como náuseas, diarreia, vômitos, queda de cabelo e fadiga (REGALADO PORRAS; CHÁVEZ NOGUEDA; POITEVIN CHACÓN, 2018). Por outro lado, a cirurgia envolve vários procedimentos como criocirurgia, ablação a laser e conização para lesões prémalignas, e histerectomia e linfadenectomia que visam eliminar o tumor em estágios mais avançados (DIO et al, 2023;GUIMARÃES et al, 2022). Infelizmente, esta técnica acarreta riscos cirúrgicos, incluindo infecção, recorrência, disfunção sexual e sangramento (DIO et al, 2023).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…No entanto, essa abordagem traz consequências indesejáveis, como náuseas, diarreia, vômitos, queda de cabelo e fadiga (REGALADO PORRAS; CHÁVEZ NOGUEDA; POITEVIN CHACÓN, 2018). Por outro lado, a cirurgia envolve vários procedimentos como criocirurgia, ablação a laser e conização para lesões prémalignas, e histerectomia e linfadenectomia que visam eliminar o tumor em estágios mais avançados (DIO et al, 2023;GUIMARÃES et al, 2022). Infelizmente, esta técnica acarreta riscos cirúrgicos, incluindo infecção, recorrência, disfunção sexual e sangramento (DIO et al, 2023).…”
Section: Resultsunclassified
“…Por outro lado, a cirurgia envolve vários procedimentos como criocirurgia, ablação a laser e conização para lesões prémalignas, e histerectomia e linfadenectomia que visam eliminar o tumor em estágios mais avançados (DIO et al, 2023;GUIMARÃES et al, 2022). Infelizmente, esta técnica acarreta riscos cirúrgicos, incluindo infecção, recorrência, disfunção sexual e sangramento (DIO et al, 2023). Por último, a radioterapia depende de radiação ionizante que pode causar cansaço e irritação da pele (CHARGARI et al, 2022).…”
Section: Resultsunclassified
“…Although radical surgery is currently the standard treatment for most early-stage CC patients, postoperative occurrence may occur partly due to insufficient radicality or potential tumor dissemination during colpotomy (13). In addition, patients with high or intermediate risk factors are found to have higher recurrence rate than others in the early-stage subpopulation (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the acupuncture point-taking characteristics of the included study revealed that the selected points were mainly based on the bladder channel of foot-taiyang, the spleen channel of foot-shaoyin, the yin channel and the liver channel of Postoperative UR in cervical cancer is generally defined as those who cannot urinate on their own or can urinate on their own but the residual urine volume is greater than 100 mL for 14 days or more after surgery (32). Currently, RH is considered to be the mainstay of treatment for early-stage cervical cancer (33). The scope of surgical resection includes the uterus, fallopian tubes, upper vagina, main ligament and complete clearance of paravaginal and pelvic lymph nodes, and during the resection process, the pelvic autonomic nerves will be destroyed, and some of the nerves that innervate the bladder will be severed, which, together with the perioperative psychosomatic condition, the change of the anatomical position of the pelvic organs, surgical anesthesia and postoperative pain, lead to bladder contraction and sensory dysfunction, as well as voiding disorders and UR (34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%